Mental representations of attachment figures facilitate recovery following upsetting autobiographical memory recall. [article]. - Selcuk, Emre
A growing literature shows that even the symbolic presence of an attachment figure facilitates the regulation of negative affect triggered by external stressors. Yet, in daily life, pernicious stressors are often internally generated-recalling an upsetting experience reliably increases negative affect, rumination, and susceptibility to physical and psychological health problems. The present research provides the first systematic examination of whether activating the mental representation of an attachment figure enhances the regulation of affect triggered by thinking about upsetting memories. Using 2 different techniques for priming attachment figure representation and 2 types of negative affect measures (explicit and implicit), activating the mental representation of an attachment figure (vs. an acquaintance or stranger) after recalling an upsetting memory enhanced recovery-eliminating the negative effects of the memory recall (Studies 1-3). In contrast, activating the mental representation of an attachment figure before recalling an upsetting memory had no such effect (Studies 1 and 2). Furthermore, activating the mental representation of an attachment figure after thinking about upsetting memories reduced negative thinking in a stream of consciousness task, and the magnitude of the attachment-induced affective recovery effects as assessed with explicit affect measures predicted mental and physical health in daily life (Study 3). Finally, a meta-analysis of the 3 studies (Study 4) showed that the regulatory benefits conferred by the mental representation of an attachment figure were weaker for individuals high on attachment avoidance. The implications of these findings for attachment, emotion regulation, and mental and physical health and discussed. -(from the author)